2007
DOI: 10.1111/j.1600-6143.2007.01900.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Antibody-Mediated Rejection Following Heart Transplantation

Abstract: Acute antibody-mediated rejection (AMR) in heart transplantation is often associated with hemodynamic compromise, and is associated with increased mortality and development of accelerated transplant coronary artery disease (TCAD). The diagnosis of AMR has historically been controversial and outcomes with aggressive immunosuppressive therapy including plasmapheresis and cyclophosphamide are poor. Advances in diagnostic techniques like the demonstration of immunopathologic evidence for antibodymediated rejection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 49 publications
0
65
0
1
Order By: Relevance
“…This compound is commonly used for the treatment of various cancers and is an immunosuppressant in organ transplantation, rheumatoid arthritis, systemic lupus erythematosus, multiple sclerosis, and other benign diseases (16). The reactive metabolites of CP chemically alkylate DNA and protein and produce cross-links, which are responsible for its cytotoxic effect (17).…”
Section: Introductionmentioning
confidence: 99%
“…This compound is commonly used for the treatment of various cancers and is an immunosuppressant in organ transplantation, rheumatoid arthritis, systemic lupus erythematosus, multiple sclerosis, and other benign diseases (16). The reactive metabolites of CP chemically alkylate DNA and protein and produce cross-links, which are responsible for its cytotoxic effect (17).…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Due to its extensive use in clinics, it possesses occupational exposure to the health care professionals. 14 Fukushima et al reported that many alkylating agents; chemotherapeutic drugs have been found to produce infertility as a result of impaired sperm production.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids or antilymphocyte antibodies are not sufficiently effective; it is necessary to eliminate the antibodies present in blood and prevent their further formation (10). The available elimination methods are plasmapheresis and immunoadsorption (11,12), both of which were successfully used in our patients.…”
Section: Original Articlementioning
confidence: 99%